2021
DOI: 10.2478/rjim-2021-0003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of coronary artery tortuosity in ischemic and non-ischemic cardiovascular pathology

Abstract: The aim of this paper was to review based on the existing literature the impact of coronary artery tortuosity on coronary pathology. Primarily, an attempt was made to establish the implication of coronary tortuosity as a physio-pathological mechanism of inducing ischemia in patients with non-obstructive coronary artery disease (CAD). Because the prevalence of tortuosity is higher in severe hypertensive patients, a second purpose of this paper was to review this association by understanding the physio-pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…This insufficiently explored entity may play a significant role in the development of ischemic signs and symptoms in patients without significant coronary obstruction. Several previous studies proposed coronary tortuosity as a potential cause of ischemia in non-obstructive CAD, but there are a lack of studies to confirm this relationship in the clinical setting [ 4 , 20 , 21 ]. A possible mechanism for developing ischemia is a reduction in distal perfusion pressure and coronary flow in the myocardial regions supplied by tortuous coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…This insufficiently explored entity may play a significant role in the development of ischemic signs and symptoms in patients without significant coronary obstruction. Several previous studies proposed coronary tortuosity as a potential cause of ischemia in non-obstructive CAD, but there are a lack of studies to confirm this relationship in the clinical setting [ 4 , 20 , 21 ]. A possible mechanism for developing ischemia is a reduction in distal perfusion pressure and coronary flow in the myocardial regions supplied by tortuous coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, postadjustment results could differ from preadjustment ones. Coronary flow impairment in these conditions is correlated with myocardial function impairment, and it does not denote a causal relationship between impaired coronary flow and myocardial dysfunction. Several factors, such as inflammation and ischemia, might accompany these conditions, leading to myocardial dysfunction 1,2,4 The literature includes a dearth of data on issues such as the diastolic function of the LV and the atrial phasic function in CSFP, CAE, and CAT.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors, such as inflammation and ischemia, might accompany these conditions, leading to myocardial dysfunction. 1,2,4 8. The literature includes a dearth of data on issues such as the diastolic function of the LV and the atrial phasic function in CSFP, CAE, and CAT.…”
Section: Caementioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies showed that coronary tortuosity may have an important role in the development of ischemic alterations in non-obstructive coronary artery disease [ 8 , 14 , 28 ]. Our study confirms this finding since we detected significantly more tortuous coronary arteries in the group of patients without significant obstruction of coronary arteries, including all three main coronary arteries.…”
Section: Discussionmentioning
confidence: 99%